2021
DOI: 10.1002/ange.202104886
|View full text |Cite
|
Sign up to set email alerts
|

High Proton‐Conductivity in Covalently Linked Polyoxometalate‐Organoboronic Acid‐Polymers

Abstract: The controlled bottom-up design of polymers with metal oxide backbones is a grand challenge in materials design, as it could give unique control over the resulting chemical properties. Herein, we report a 1D-organo-functionalized polyoxometalate polymer featuring a purely inorganic backbone. The polymer is self-assembled from two types of monomers, inorganic Wells-Dawson-type polyoxometalates, and aromatic organo-boronates. Their covalent linkage results in 1D polymer strands, which combine an inorganic oxide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…This procedure has been extended to a variety of carbon substrates, including multiwalled carbon nanotubes (MWCNT), graphene, CB, and carbon fibers, as reviewed by Genovese and Lian Covalent bonding is an important approach for the fabrication of POM/polymer hybrid materials. Thus, the obtained hybrid materials possess relatively high strength and stability, making them suitable for practical applications [107]. Streb et al reported a onedimensional (1D)-organo-functionalized POM/polymer through a covalent link [108] PPy chain (Fig.…”
Section: Poms/nanocarbon Nanohybridsmentioning
confidence: 99%
“…This procedure has been extended to a variety of carbon substrates, including multiwalled carbon nanotubes (MWCNT), graphene, CB, and carbon fibers, as reviewed by Genovese and Lian Covalent bonding is an important approach for the fabrication of POM/polymer hybrid materials. Thus, the obtained hybrid materials possess relatively high strength and stability, making them suitable for practical applications [107]. Streb et al reported a onedimensional (1D)-organo-functionalized POM/polymer through a covalent link [108] PPy chain (Fig.…”
Section: Poms/nanocarbon Nanohybridsmentioning
confidence: 99%
“…The transition metals in the host cluster possess outstanding redox ability, which can achieve electron/ion receiving and donation without affecting their own structure. Therefore, they present many physicochemical properties superior to common metal oxides and mononuclear complexes and are widely used in catalytic chemistry, photoelectrochemistry, medicinal chemistry, polymer conductor materials, magnetism, and other fields. The specific atomic composition and molecular structure of POMs endows them with strong coordination ability, structural tailorability, and performance tunability. The flexible modification and assembly of POMs using functional organic ligands and various metals can yield various POM derivatives with unique structures such as 3D networks with pores, host–guest structures, and open frameworks.…”
Section: Introductionmentioning
confidence: 99%